Novel S-N curve for different hardened layers in point and line contact. (December 2021) - Trausmuth, A.; Grün, F.
Highlights: Generation of a novel S-N curve for different materials and hardness layers. S-N curves from point and line contact tests of different materials and hardenend layers. Influence of different counter body materials. Influence of SRR, roughness and plastic deformations on life time at S-N curve. Abstract: Rolling contact fatigue (RCF) regularly causes mechanical components to fail under cyclic loads. Popular surface treatment processes such as case hardening (carburization), nitriding and tempered martensitic reduce the effect of RCF damage. This paper presents multi-stage S-N curve for steels with different surface treatments, under point and line contact conditions using RCF tribometers for the experiments and finite element (FEM) simulation to simulate localised stresses in the contacts. Additionally, S-N tests with 0, 5 and 11% slide to roll ratio (SRR) are presented. This work demonstrates the importance of testing key points at RCF S-N curves to optimize the hardened layers.